2004
DOI: 10.1523/jneurosci.1558-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dopamine Function in Primates Using Pharmacologic Magnetic Resonance Imaging

Abstract: Dopamine (DA) receptors play a central role in such diverse pathologies as Parkinson's disease, schizophrenia, and drug abuse. We used an amphetamine challenge combined with pharmacologic magnetic resonance imaging (phMRI) to map DA-associated circuitry in nonhuman primates with high sensitivity and spatial resolution. Seven control cynomolgous monkeys and 10 MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-treated parkinsonian primates were studied longitudinally using both positron emission tomography (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 47 publications
(59 reference statements)
8
84
2
Order By: Relevance
“…These imaging studies confirmed mGluR5 binding to DA target regions (Fig. 1f) matching cortical and subcortical areas with identical distribution to that we described previously using fMRI and amphetamine (Jenkins et al, 2004) (i.e. the areas in which DA release induces an increase in regional cerebral blood volume).…”
supporting
confidence: 87%
See 4 more Smart Citations
“…These imaging studies confirmed mGluR5 binding to DA target regions (Fig. 1f) matching cortical and subcortical areas with identical distribution to that we described previously using fMRI and amphetamine (Jenkins et al, 2004) (i.e. the areas in which DA release induces an increase in regional cerebral blood volume).…”
supporting
confidence: 87%
“…The loss of [ 11 C]CFT binding was directly correlated with the severity of the parkinsonian signs (p < 0.005) measured by the global motor score in a rating scale based on the motor subscale of the UPDRS (Fig. 1e) as we have previously described in this model (Jenkins et al, 2004). To confirm that the change in [ 11 C]MPEPy binding reflected changes in mGluR5, we examined in 2 other primates, the distribution of the novel compound [ 18 F]FPEB (Hamill et al, 2005;Wang et al, 2007), which has exceptionally high affinity to mGluR5.…”
supporting
confidence: 59%
See 3 more Smart Citations